Continuities and disruptions in Islamic education: biographies of shogirds from Tajikistan - Roche, Sophie (Anthropology of the contemporary Middle East and Central Eurasia, 2013)
The circumstances in which Islam has been able to survive the atheistic policies of the Soviet Union have been much debated throughout the last two decades. The study of authorities and institutions has highlighted numerous well-known successful religious authorities and groups that maintained religious networks throughout that period. However, many religious individuals have found navigating this period more problematic. What about those students who started their studies, but then succumbed to the political waves of suppression and conflict, and never satisfactorily completed their education? What have they become and how did they use the knowledge they did acquire? I have investigated these questions by means of biographies of ordinary people who took Islamic lessons at some point in their lives. Those presented in this article reveal the three central relations that helped religious education to adapt to the various political changes: the dual teacher-student (ustod-shogird) relationship, the social group (village community) and the network of scholars. The educational system of rotating students among religious scholars continues to this day to be the main available avenue for religious education for thousands of young men who continue to navigate their educational career through different political epochs.
Gesehen am 11.12.2017